Educação especial na EJA: análise do processo de construção da prática docente - Nogueira, Marcela Fontão (2020)
The present study brought as main questioning the way teachers of the regular classroom build their practice, their teaching work with student’s public target of special education (EPAEE), considering their training initial, continuous and in service. The general objective was analyze the narratives of the teachers about the process of training and pedagogical practices and specific objectives identify the types of initial and continuous training of teachers in the regular classroom; analyze the training in service offered in the school and analyze how the teachers perceive and reflect their performance in front of the EPAEE in an Integrated Youth and Adult Education Center (CIEJA) of the municipal education network in the city of São Paulo. We used the qualitative approach, and this exploratory research is, type case study. The instruments for data collection were a questionnaire with closed questions and the written record of the training in service and the planning of classes and teaching performance. Data analysis was structured from the coding cycles, with the aid of ATLAS.ti qualitative analysis software. The participants were divided into two groups, one with those who had some type of initial or continuing training in Special Education (EE) and with those who did not have it. For each of the narratives there were three distinct codes, which dialogued both with the teachers' speech and with the theoretical framework adopted in this study: Paulo Freire and the Pedagogy of the Oppressed. As results we found that the initial training in EJA and Special Education contemplated less half of the participants, the same occurred with the continuing training in EE, despite the advantages that this training can bring to career evolution teaching. Regarding the training in service, this proved to be effective regarding support emotional and specific learning, but insufficient in frequency. There was no significant difference in the narratives of the two groups, which indicates that the practice teacher, if conscious and problematizing, added to the training in service can mitigate any lags in the initial and/or continuous formation. The results of analysis of teacher planning and practice indicated that teachers made the curriculum more flexible through reflection on practice itself, which used dialogue both in planning and practices, valuing the knowledge of students and finally did so collaboratively, building their teaching practice in partnership with other teachers and with the students themselves.